Designing an IoT-Based Food Monitoring Application for Chicken Farming - Ilham Widayanto; Adam Sekti Aji (Kirana Publisher (KNPub), 2025)
Many broiler farming industries in Indonesia still use traditional methods in feed management, which often cause inefficiencies and human errors. Without modern solutions, these problems can have a negative impact on livestock productivity and health, as well as increase operational costs. This research aims to develop an Internet of Things (IoT)-based feed monitoring application that can monitor feed stocks in real-time, set automatic feeding schedules, and analyze feed consumption data to increase efficiency, accuracy, and overall productivity. Interim results show that the feed monitoring application with IoT technology is able to provide accurate and detailed information in real-time, reduce human error, and increase operational efficiency significantly. It is hoped that the implementation of this innovative application can help farmers optimize feed management, increase livestock productivity, enhance animal welfare, and reduce operational costs in a sustainable manner.